КОНСТРУИРОВАНИЕ КОМПОЗИЦИИ, ОБЛАДАЮЩЕЙ ВЫСОКОЙ БИОЛОГИЧЕКОЙ АКТИВНОСТЬЮ, НА ОСНОВЕ РИСОВОЙ ШЕЛУХИ И ЦИАНОБАКТЕРИИ SPIRULINA PLATENSIS Казахский национальный университет им. аль-Фараби, г. Алматы (Experimental biology, 2015)
The effect of carbonized rice shell in combination with Spirulina platensis СALU-532 m on growth and viability of rat intestine epithelial cell culture IEC-6 is studied.
Keywords: carbonized; IEC-6 is studied.